2009
DOI: 10.1371/journal.pbio.1000045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Chloroplast Protein Kinase Stt7 during State Transitions

Abstract: State transitions allow for the balancing of the light excitation energy between photosystem I and photosystem II and for optimal photosynthetic activity when photosynthetic organisms are subjected to changing light conditions. This process is regulated by the redox state of the plastoquinone pool through the Stt7/STN7 protein kinase required for phosphorylation of the light-harvesting complex LHCII and for the reversible displacement of the mobile LHCII between the photosystems. We show that Stt7 is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
182
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 156 publications
(193 citation statements)
references
References 52 publications
8
182
2
1
Order By: Relevance
“…Excess excitation of PSII relative to PSI leads to reduction of the PQ pool and thus favors the docking of PQH 2 to the Qo site of the Cyt b 6 f complex. This process activates the Stt7/STN7 protein kinase (Vener et al, 1997;Zito et al, 1999), which is closely associated with this complex and leads to the phosphorylation of some LHCII proteins and to their detachment from PSII and binding to PSI (Depège et al, 2003;Lemeille et al, 2009). Although both Lhcb1 and Lhcb2 are phosphorylated, only the phosphorylated form of Lhcb2 is associated with PSI whereas phosphorylated Lhcb1 is excluded from this complex (Longoni et al, 2015).…”
mentioning
confidence: 99%
“…Excess excitation of PSII relative to PSI leads to reduction of the PQ pool and thus favors the docking of PQH 2 to the Qo site of the Cyt b 6 f complex. This process activates the Stt7/STN7 protein kinase (Vener et al, 1997;Zito et al, 1999), which is closely associated with this complex and leads to the phosphorylation of some LHCII proteins and to their detachment from PSII and binding to PSI (Depège et al, 2003;Lemeille et al, 2009). Although both Lhcb1 and Lhcb2 are phosphorylated, only the phosphorylated form of Lhcb2 is associated with PSI whereas phosphorylated Lhcb1 is excluded from this complex (Longoni et al, 2015).…”
mentioning
confidence: 99%
“…In fact, this kinase could never be detected in free form upon mild solubilization of thylakoid membranes. Immunoprecipitations revealed that this kinase is also associated with LHCII and PSI but no stable association with PSII could be detected [32]. An intriguing structural feature of Stt7/STN7 is the Model of Stt7/STN7 kinase in the thylakoid membrane.…”
Section: Role Of Stt7/stn7 Kinasementioning
confidence: 98%
“…The Stt7/STN7 kinase contains a transmembrane domain that separates its N-terminal part in the lumen from the catalytic kinase domain on the stromal side of the thylakoid membrane (figure 2) [32]. This kinase is firmly associated with the cyt b 6 f complex.…”
Section: Role Of Stt7/stn7 Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…Whereas land plants mobilize only 15-20% of the LHCII pool, state transitions in the alga Chlamydomonas reinhardtii have been reported to involve up to 80% of the LHCII antennae [35]. Some regulatory features of the LHCII kinase (Stt7/STN7) are shared between algae and land plants, such as its decreased activity under high light stress [36][37][38] and its activation by the binding of plastoquinol to Cytb6f [39][40][41]. It is currently unknown whether the LHCII phosphatase PPH1/TAP38 [42,43] is regulated, and specific orthologues have not been characterized outside the land plant lineage.…”
Section: Introductionmentioning
confidence: 99%